Hunger for profit: how food delivery platforms manage couriers in China - Chan, Jenny (Sociologias, 2021)
How do food delivery platform firms, such as Meituan (operated by Tencent) and Ele.me (owned by Alibaba), manage couriers through service contracting rather than formal employment? How do couriers experience control and autonomy at work? Using observation and interviews, the author finds that a combination of data-driven surveillance systems and customer feedback mechanisms are incentivizing workers’ efforts. Corporate utilization of both manual and emotional labor is critical to realizing profits. Individual freedom is framed in a way that crowdsourced couriers are not required to work a minimum amount of time. Flexibility enabled by the algorithmic management, however, cuts both ways. When there is less demand, the platform corporations automatically reduce their dependence on labor. With variable food orders and piece rates, workers’ minimum earnings are not guaranteed. In the absence of Chinese legal protections over the fast-growing food delivery sector, informal workers are desperately struggling for livelihood.